SPECIES‐SPECIFIC DIFFERENCES IN ADAPTIVE PHENOTYPIC PLASTICITY IN AN ECOLOGICALLY RELEVANT TROPHIC TRAIT: HYPERTROPHIC LIPS IN MIDAS CICHLID FISHES. (18th February 2014) - Machado‐Schiaffino, Gonzalo; Henning, Frederico; Meyer, Axel
<x xml:space="preserve">Abstract</x> The spectacular species richness of cichlids and their diversity in morphology, coloration, and behavior have made them an ideal model for the study of speciation and adaptive evolution. Hypertrophic lips evolved repeatedly and independently in African and Neotropical cichlid radiations. Cichlids with hypertrophic lips forage predominantly in rocky crevices and it has been hypothesized that mechanical stress caused by friction could result in larger lips through phenotypic plasticity. To test the influence of the environment on the size and development of lips, we conducted a series of breeding and feeding experiments on Midas cichlids. Full‐sibs of Amphilophus labiatus (thick‐lipped) and Amphilophus citrinellus (thin‐lipped) each were split into a control group which was fed food from the water column and a treatment group whose food was fixed to substrates. We found strong evidence for phenotypic plasticity on lip area in the thick‐lipped species, but not in the thin‐lipped species. Intermediate phenotypic values were observed in hybrids from thick‐ and thin‐lipped species reared under "control" conditions. Thus, both a genetic, but also a phenotypic plastic component is involved in the development of hypertrophic lips in Neotropical cichlids. Moreover, species‐specific adaptive phenotypic plasticity was found, suggesting that plasticity is selected for in recent thick‐lipped species.